The 'Logos' of Faith in the Era of Pope Francis. (November 2019) - Gamberini, Paolo
Through globalization and greater exchange, religious identities are meeting and facing each other on a regular basis and in a very rapid way. As intercultural and religious plurality made possible the rise of Christianity, so in our age Christians must continue to be in dialogue with the secular world and other faith traditions, and be ready to move beyond an apologetic and exclusive form of self-understanding. Pope Francis's magisterium is challenging the Catholic church to 'reform' its identity, envisioning the logos for Christian faith in discernment, reconciliation, and transformation, so that through a theology of encounter Christians will better understand their faith, redefine their confessional boundaries in a dialogical way, and become bridge-builders in our contemporary pluralistic society.